Effect of Arbuscular Mycorrhizal Fungi Isolated From Rock Phosphate Mine and Agricultural Soil on the Improvement of Wheat Plant Growth - Hazzoumi, Zakaria; Azaroual, Salah Eddine; El Mernissi, Najib; Zaroual, Youssef; Duponnois, Robin; Bouizgarne, Brahim; Meftah Kadmiri, Issam (Frontiers in Microbiology, 2022)
This work is aiming to isolate and investigate mycorrhizal spores from a natural rock phosphate mine in the vicinity of some native plants, and agricultural soil. Spores were isolated and multiplied before being used in the assay on wheat plants, in order to assess their capacity in increasing the growth, nutritional profile improvement, and biochemical parameters in the inoculated plants. Results showed a high diversity of isolated arbuscular mycorrhizal fungi (AMF) spores in the agricultural soil, and less diversity in the natural phosphate samples, where three main genera were identified; Glomus, Gigaspora, and Acaulospora. The inoculation of wheat plants with AMF spores improved the plants' growth, via the increased density of the root system, especially in mycorrhizal plants with triple superphosphate (TSP) or natural rock phosphate (RP) phosphorus fertilization regime. The improvement of the physiological and biochemical parameters (chlorophyll contents and phenolic compound) of the treated plants reflected the positive impact of AMF, especially those originating from RP. Results showed Also an impact of applied treatments on the phosphate uptake, which explained the positive effects shown in the mycorrhizal wheat plants with rock phosphate. AMF in phosphate mine could be an important source of inoculum to improve plant nutrient efficiency with the direct use of RP as fertilizer.